2018
DOI: 10.1002/ajp.22744
|View full text |Cite
|
Sign up to set email alerts
|

Small but wise: Common marmosets (Callithrix jacchus) use acoustic signals as cues to avoid interactions with blonde capuchin monkeys (Sapajus flavius)

Abstract: Vocalizations are often used by animals to communicate and mediate social interactions. Animals may benefit from eavesdropping on calls from other species to avoid predation and thus increase their chances of survival. Here we use both observational and experimental evidence to investigate eavesdropping and how acoustic signals may mediate interactions between two sympatric and endemic primate species (common marmosets and blonde capuchin monkeys) in a fragment of Atlantic Rainforest in Northeastern Brazil. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In marmosets, vocalization is as important as other species. Studies have shown that specific vocalizations can be used by marmosets to avoid contact with other species in the wild (46). Thus, learning the correct usage of vocalizations is imperative to the animal's safety in their natural habitat.…”
Section: Discussionmentioning
confidence: 99%
“…In marmosets, vocalization is as important as other species. Studies have shown that specific vocalizations can be used by marmosets to avoid contact with other species in the wild (46). Thus, learning the correct usage of vocalizations is imperative to the animal's safety in their natural habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Vocal communication is paramount for the survival of many species. Primates and other animals use vocalizations to navigate courtship, locate food sources, and communicate the presence of predators (Bastos et al., 2018 ; Caruso et al., 2020 ). Thus, several behavioral tests have been developed to identify the neural substrates responsible for communication in different social situations and assess deficits in communication (Caruso et al., 2020 ; Shair et al., 2012 ; Muller & Shair, 2016 ; Tschida et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%